Promoting tertiary level students' critical thinking through the use of Socratic questioning on the blog - Shahsavar, Zahra; Tan, Bee Hoon; Yap, Ngee Thai; Abu Samah, Bahaman (Universiti Putra Malaysia Press, 2013)
Over the past decade, much has been done to improve students' critical thinking in education. This study investigates if applying Socratic questioning on the blog can promote students' critical thinking. It applies a generic model, which associates with three fundamental components. Participants were an intact class of tertiary level students enrolled in an obligatory course. Students practiced Socratic questioning during face-to-face and online sessions. To serve this goal, they were asked to be attentive and share their ideas or questions with other students on the blog. Students' critical thinking ability was assessed using the Cornell Critical Thinking Test before and after they were trained in Socratic questioning. The results showed that the Socratic questioning training had a significant positive change on students' critical thinking ability. If students master the art of Socratic questioning, they can bring it into various courses they take. They can also use it in different discussions they engage in, and apply it not only in raising and asking questions about what is taught, but also in making questions concerning the issues in their daily life in a meaningful way.